Joy in “Happiness”: A Semiotic Analysis - Agustina, Mia Fitria; Camelia, Royan; Trisnawati, Ririn Kurnia (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2025)
This study aims to determine the meaning of happiness in the short movie “Happiness” by Steve Cutts. In interpreting the happiness, this study uses Saussure’s Semiotics theory. This study employed a qualitative method. The discussion of this study is divided into billboards, food and beverages billboards/brochures, fashion billboards and brochures, and medicines billboards. The results of this study indicated that happiness because of alcohol, food, beverages, fashion, and drugs are temporary. The effect of happiness that is obtained is instant, where happiness is easy to get but also easy to lose, it will not last long. From the results of this study, it can be understood that the meaning of happiness in real life and even in the short movie “Happiness” cannot be taken lightly since being happiness is something that we feel rather than what we think.